Why Should a Firm Choose to Limit the Size of Its Market Area? - Marco Alderighi (European Regional Science Association (ERSA), 2006)
We analyze a variant of the standard Dixit-Stiglitz (AER, 1977) model, adding transport costs and assuming that, in addition to price, a firm can choose the size of the market area and the quality of the product. We also modify the standard cost function, making variable costs and fixed costs increasing in both "reach" and quality. We characterize the solution of the model and we find the conditions under which a firm decides to limit the market area. Finally, we show that the firm's behavior is constrained socially optimal.
Keywords: 330